[PP.35.02] EFFECT OF ANGIOTENSIN RECEPTOR STIMULATION IN THE ROSTRAL VENTROLATERAL MEDULLA ON BLOOD PRESSURE IN NORMOTENSIVE RATS: INTERACTION WITH GLUTAMATE AND GAMMA-AMINOBUTYRIC ACID. (September 2016) - Legat, L.; Brouwers, S.; Smolders, I.; Dupont, A.D.
Abstract : Objective: There is increasing evidence that glutamate and gamma-aminobutyric acid (GABA) interact within the rostral ventrolateral medulla (RVLM) modulating the central regulation of blood pressure and sympathetic tone. Angiotensin II (Ang II) is the most important effector in the renin-angiotensin-aldosterone system (RAAS) mediating its actions through the angiotensin II type 1 receptor (AT1R) and angiotensin II type 2 receptor (AT2R). The AT2R is part of the protective arm of the RAAS and mediates opposing effects counterbalancing the AT1R mediated actions. The selective and specific AT2R agonist Compound 21 (C21) is a useful research tool to investigate the AT2R mediated effects. Design and method: In the present study we assess through local stimulation and blockade of AT1R and AT2R the possible role of the brain RAAS at the level of the RVLM on the regulation of blood pressure. In vivo microdialysis, for measurement of extracellular glutamate and GABA levels, was carried out in the RVLM of conscious normotensive Wistar rats while locally infusing C21, Ang II, and PD123319. Glutamate and GABA levels were quantified by HPLC. Subsequently, the effect of central administration of C21, Ang II, and PD123319 on mean arterial pressure was assessed with a pressure transducer for continuous monitoring. Results: Infusion of Ang II into the RVLM significantly increased glutamate levels (P < 0.05) and significantly decreased GABA levels (P < 0.01). Infusion of the AT2R agonist C21 (0.05 μg/μl/h) tended to decrease glutamate and increase GABA levels, while absolutely no change was seen when co-infusing C21 together with the AT2 receptor antagonist PD123319. C21 infusion (0.05 μg/μl/h) significantly lowered blood pressure (P < 0.01). These responses were abolished by co-administration of C21 and PD123319. No changes in neurotransmitter levels or effects on blood pressure were seen with PD123319 infusion alone. Conclusions: These data demonstrate that acute specific stimulation of AT2R in the RVLM by local C21 infusion reduces blood pressure in normotensive rats, and suggests that decreases in local glutamate and increases in GABA levels may be involved in the sympatho-inhibitory action underlying this hypotensive response.